2020
DOI: 10.18844/gjflt.v10i2.4665
|View full text |Cite
|
Sign up to set email alerts
|

EFL written competence through twitter in mobile version in compulsory secondary education

Abstract: The use of Information and Communication Technologies (henceforth, ICT) in foreign language learning and, to be more specific, in English language learning has increased quite considerably since the commencement of the 21st century and, particularly, in the second decade of the 21st century with the introduction of mobile learning (m-learning, henceforth) at our daily lives. Our aim, at this current paper, is to confirm whether use of the Twitter social network via a mobile device helps Spanish learners of Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…On the other hand, the deficiency of oral English language education and lack of exposure to English communication environment for international students from Asian context might negatively affect them as they would have diverse oral communication problems when studying in English-medium higher institutions [42]. A cohort of Asian students encounter many communicative challenges in English language for academic purpose as they are not able to experience the face-to-face communication opportunities due to online learning and remote teaching, which will impede their academic progress [20].The deficiency of oral English competence decreases their confidence and willingness to communicate actively and effectively with lecturers and their peers [42].As they engage in their courses online, they might also be afraid of making mistakes in expressing themselves in English language in avoidance of getting negative feedback from others [26].…”
Section: Research On the Importance Of English Language Communication Competence For Efl Undergraduate Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the deficiency of oral English language education and lack of exposure to English communication environment for international students from Asian context might negatively affect them as they would have diverse oral communication problems when studying in English-medium higher institutions [42]. A cohort of Asian students encounter many communicative challenges in English language for academic purpose as they are not able to experience the face-to-face communication opportunities due to online learning and remote teaching, which will impede their academic progress [20].The deficiency of oral English competence decreases their confidence and willingness to communicate actively and effectively with lecturers and their peers [42].As they engage in their courses online, they might also be afraid of making mistakes in expressing themselves in English language in avoidance of getting negative feedback from others [26].…”
Section: Research On the Importance Of English Language Communication Competence For Efl Undergraduate Studentsmentioning
confidence: 99%
“…With the development of Web-2.0 and computer technology, social media applications have now been widely used in education field [4].Specifically the kinds of social media applications integrated with short videos that could help provide interesting mode of learning English language communication competence for EFL language learners in the current digital arena in response to the impacts of Covid-19 pandemic on English language education [39].Previous related studies have indicated the benefits of using social media applications for English language communication education purpose such as Instagram, WhatsApp, Twitter as well as China-made Wechat and Weiblog [2,4,23,26,47].…”
Section: Using Tiktok In Teaching English Language Communication Competencementioning
confidence: 99%
“…Recent studies in MALL portrayed positive acceptance among secondary school learners in mobile learning to enhance their English language. In [28], researchers studied the writing competency of English as a foreign language (EFL) among learners in a secondary school setting, using Twitter as part of the writing curriculum, and reported that learners used more word expressions and had an improved quality of summary-writing. Likewise, a study by [29] examined the use of the instant messaging app Telegram to improve the EFL grammar accuracy of female adult learners.…”
Section: Trends In Mobile Learningmentioning
confidence: 99%
“…The study of the self-assessment influence covers a wide range of applications, including written works in English (Montaner, 2020), sociological studies (Radid, Lotfi & Akoul, 2020), mathematics (Stallings & Tascione, 1996), natural sciences, and External evaluation of educational achievements (Akoul, Lotfi & Radid, 2021). In each case, the students were engaged in written forms of self-assessment with the use of test papers and tests, as well as oral forms of self-assessment.…”
Section: Literature Reviewmentioning
confidence: 99%